2011
DOI: 10.1074/jbc.m111.227082
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between the Androgen Receptor and the Liver X Receptor

Abstract: High cholesterol levels are associated with prostate cancer development. Androgens promote cholesterol accumulation by activating the sterol-regulatory element-binding protein isoform 2 (SREBP-2) transcription factor. However, SREBP-2 is in balance with the liver X receptor (LXR; NR1H2/NR1H3), a transcription factor that prevents cholesterol accumulation. Here, we show that LXR activity is down-regulated by the androgen receptor (AR; NR3C4). In turn, this reduces LXR target gene expression. This antagonism on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 62 publications
3
53
0
Order By: Relevance
“…34). Growth factors involving signaling via the androgen receptor or Akt can also up-regulate cholesterogenic genes, but this occurs indirectly, through activation of SREBP-2 (35,36).…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…34). Growth factors involving signaling via the androgen receptor or Akt can also up-regulate cholesterogenic genes, but this occurs indirectly, through activation of SREBP-2 (35,36).…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…Since it has been reported that LXR activation decreased intracellular cholesterol levels (13,40), it was possible that changes in hOAT1 activity might be secondary to changes in cellular cholesterol levels. This notion came from the study of Dias and Ribeiro (5), who reported that cholesterol regulated gene expression of OCT1 (SLC22A1) and Na ϩ -bile acid cotransporter NTCP (SLC10A1) in HepG2 cells (5).…”
Section: Expression Of Lxr␣ and Lxr␤ In S2-hoat1 Cellsmentioning
confidence: 99%
“…There is recognized physiologic interplay between the LXR and ER ligand/receptor systems. LXR activation influences the synthesis and metabolism of estrogen (22,23), estrogen causes attenuated expression of LXRα and its target genes in white adipose tissue (24), and estrogen also antagonizes LXR transcriptional activity in breast cancer cells (25). However, direct functional partnership between LXR and ER has not been previously observed in any biological context.…”
Section: Introductionmentioning
confidence: 98%